Spatio-temporal distribution of seagrass extent in three zones of Spermonde Archipelago, Indonesia - ST. FIRJATIH WIDHAH; ROHANI AMBO-RAPPE; LUKY ADRIANTO (Society for Indonesian Biodiversity, 2026)
Abstract. Widhah SF, Ambo-Rappe R, Adrianto L. 2026. Spatio-temporal distribution of seagrass extent in three zones of Spermonde Archipelago, Indonesia. Biodiversitas 27 (2): d270216. https://doi.org/10.13057/biodiv/d270216. Seagrass meadows are vital blue carbon habitats that support biodiversity, fisheries, and coastal defense, but human activities and environmental changes increasingly threaten them. This research examined how seagrass distribution shifted over time and space across Barrang Lompo, Badi, and Langkai Islands in the Spermonde Archipelago, Indonesia, representing inner, middle, and outer zones. Using supervised classification of Sentinel-2 satellite images from 2015 and 2025, validated by field observations, we identified distinct regional patterns of seagrass loss over a decade. Area measurements included 95% confidence intervals, and all observed declines were confirmed by field data. Over ten years, seagrass cover shrank by 12.53 hectares (30.69%) in Barrang Lompo, 3.91 hectares (56.02%) in Badi, and 12.23 hectares (26.86%) in Langkai. Major losses were noted in Barrang Lompo and Badi due to dense populations, intensive fishing, land-use change, and pollution, while oceanographic factors like strong currents, sediment buildup, and variable water quality mainly drove Langkai’s decline. These spatial patterns demonstrate the combined impacts of human stressors and environmental factors on seagrass decline and underscore the necessity for targeted conservation efforts, water quality improvements, and zone-specific fisheries management to protect blue carbon functions and ecosystem resilience in the Spermonde Archipelago.